Exposure of Social Media Advertising Media to Corn Farmers - Ali Alamsyah Kusumadinata; Astrid Sri Wahyuni Sumah; Suryatna, Undang (PT FORMOSA CENDEKIA GLOBAL, 2023)
Agriculture has an important role in improving food security and food availability which is also a source of income for farming communities in the village. The decision of farmers in cultivation has started from one month of planting. This activity is carried out by farmers to ensure good results. This study uses a quantitative approach that looks at farmers' activities in media exposure on social media related to managed farming. The farmers who were respondents were South Sumatran farmers in two districts of Ogan Ilir and Banyuasin. Sampling of 100 people by considering the adequacy of data to generalize. The data extracted is seen from the use of social media and the management of cultivation carried out. The results showed that the use of social media was carried out more than the entertainment used by farmers. Very few farmers use social media as part of decision-making considerations. Decisions are taken from the accumulation of information received directly by farmers and conditions in the field